EFEKTIVITAS PROGRAM SOSIALISASI DALAM MEMPERMUDAH PROSES PENERBITAN NIB BAGI PELAKU UMKM DI DESA PANGKIL - Syarifah Widia; Zhahara Dwi Amanda; Wisnu Aryadi; Yessy Ramawati Shaputri; Zhafira Aini; Merwina Waruwu; Ilil Arifatin; Windy Pratiwi; Wiky Dwipa Abial; Zuleha Zuleha (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Bima, 2026)
MSME actors in Pangkil Village face obstacles in the process of issuing a Business Identification Number (NIB) due to the lack of socialization and limited access to technology. This study aims to assess the effectiveness of the socialization program in facilitating the NIB issuance process for MSME actors. Qualitative methods were used with data collection through interviews, observations, and focus group discussions. The results showed that the socialization program and technical assistance succeeded in increasing the understanding of MSME actors and increasing the number of MSMEs that have NIB from 30% to 60%, while encouraging positive social changes related to business legality awareness in the community.